2004
DOI: 10.1074/jbc.m404417200
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylamine Assimilation by Rhodobacter capsulatus E1F1

Abstract: Rhodobacter capsulatus E1F1 grows phototrophically with nitrate as nitrogen source. Using primers designed for conserved motifs in bacterial assimilatory nitrate reductases, a 450-bp DNA was amplified by PCR and used for the screening of a genomic library. A cosmid carrying an insert with four SalI fragments of 2.8, 4.1, 4.5, and 5.8 kb was isolated, and DNA sequencing revealed that it contains a nitrate assimilation (nas) gene region, including the hcp gene coding for a hybrid cluster protein (HCP). Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 49 publications
0
35
0
2
Order By: Relevance
“…The only exception seems to be R. capsulatus E1F1, whose genome contains an nsrR ortholog close to the hcp gene within the nitrate assimilation nas gene cluster [17]. However, in denitrifying species, including R. sphaeroides and B. japonicum, the FNR-like transcriptional factor NnrR activates expression of nitrite and NO reductases and of the nnrS gene [3638].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The only exception seems to be R. capsulatus E1F1, whose genome contains an nsrR ortholog close to the hcp gene within the nitrate assimilation nas gene cluster [17]. However, in denitrifying species, including R. sphaeroides and B. japonicum, the FNR-like transcriptional factor NnrR activates expression of nitrite and NO reductases and of the nnrS gene [3638].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies demonstrated oxygen-sensitive hydroxylamine reductase activity of the E. coli Hcp protein, suggesting its possible role in detoxification of reactive by-products of nitrite reduction [16]. More recently, the requirement of the hcp gene for in vivo hydroxylamine reduction was observed in Rhodobacter capsulatus E1F1 [17]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optimal conditions of the oxygen-sensitive hydroxylamine reductase activity of R. capsulatus HCP (13), as well of the E. coli HCP (14), could only be found at pH 9. The anaerobically purified D. desulfuricans HCP also exhibited a very high K m value for hydroxylamine at neutral pH (15).…”
mentioning
confidence: 99%
“…Moreno-Vivian and collaborators (13) reported the increase of anaerobic tolerance to hydroxylamine of E. coli cells overproducing Rhodobacter capsulatus HCP. However, the optimal conditions of the oxygen-sensitive hydroxylamine reductase activity of R. capsulatus HCP (13), as well of the E. coli HCP (14), could only be found at pH 9.…”
mentioning
confidence: 99%